New method for sintering silica frits for capillary microcolumns - Keunchkarian, Sonia (2014)
One of the main steps in the manufacture of robust and efficient packed capillary microcolumns for electro- and capillary chromatography is the generation of porous devices to retain the packed beds. Frits based on sintered silica particles have been found to give the best results in terms of mechanical resistance and efficiency. The conventional procedure to produce these kinds of frits consists in a radial heating of the packed material with either a flame or an electrical resistance, but the frits thus obtained have many drawbacks as a result of the procedure rather than the silica per se as the base material. In the present work we investigated a new approach to produce silica-based retaining devices involving the frontal exposure of a short silica-particle bed packed at the end of a capillary tube. The capillary is radially insulated and frontally exposed to the heat of a muffle oven, generating a transfer of heat that is not radial but rather throughout the capillary axis. This procedure resulted in substantial advantages: an improved radial homogeneity, a protection of the external polyimide, and a generation of extremely short (400–600 m) frits that were highly permeable and avoided bubble formation.